Child Maltreatment Increases the Risk of Self-esteem Impairment: Findings from Children and Adolescents in Uganda - Ndyareeba, Eunice; Ainamani, Herbert E.; Ankunda, Grace; Amanya, Agnes (East African Journal of Health and Science, 2023)
Child maltreatment exposes children to developmental risks pertaining to internalizing problems both in early and later life. However, research on this phenomenon in low- and middle-income countries is scanty. Our study aimed at examining the association between different forms of child maltreatment and self-esteem among children and adolescents in Uganda. The present investigation involved conducting interviews with a cohort of 232 school-going children and adolescents. The Maltreatment and Abuse Chronology Exposure Pediatric-Version (MACE) questionnaire was employed to evaluate the various forms of maltreatment that the participants may have encountered. Furthermore, the Rosenberg Self-esteem Scale (RSE) was utilized to gauge their self-esteem. To explore the association between diverse maltreatment categories and self-esteem levels, descriptive statistics were employed, and linear regression analysis was conducted using SPSS. Our results showed that the majority 162 (70%) of the children had low self-esteem and high levels of childhood maltreatment (M = 28.7, SD = 2.16). The study found a statistically significant inverse relationship between child maltreatment and self-esteem (b -0.012, p=-.0.0025). It was also found that the regression model was statistically significant and therefore the data fits the model (F = 5.82, E = .017). The regression equation indicated that for every unit increase in child maltreatment, self-esteem decreases by 1.3%. It was concluded that maltreatment has a negative detrimental impact on the self-esteem of children and adolescents. The study contributes to the existing knowledge base and its implications for intervention, support, and prevention efforts in the context of child maltreatment.